First report of Blastocystis sp. and Enterocytozoon bieneusi in raptors - Gao, Zhen-Qiu; Qin, Si-Yuan; Xie, Lin-Hong; Bao, Guang-Rong; Wang, Xingzhou; Qin, Ya; Han, Xuetao; Yu, Xiaoming; Lei, Cong-Cong; Zhang, Xiao-Tian; Yu, Ming-Yuan; Sun, He-Ting; et al. (Frontiers in Veterinary Science, 2025)
IntroductionBlastocystis sp. and Enterocytozoon bieneusi are common zoonotic pathogens threatening human and animal health. These parasites are widely distributed in birds, and substantial research on their prevalence has been conducted. However, no studies on Blastocystis sp. and E. bieneusi in raptors exist.MethodsThe present study collected 335 fecal samples from raptors in Changdao, China. The prevalence and genotypes of Blastocystis sp. and E. bieneusi were determined through amplification of SSU rRNA and ITS gene. Phylogenetic analysis was performed using MEGA 11 with the neighbor-joining method (Kimura 2-parameter model, 1000 replicate).ResultsThe overall infection rates of Blastocystis sp. and E. bieneusi in raptors were 1.19% (4/335) and 1.79% (6/335), respecttively. Among them, the highest infection rate of Blastocystis sp. was observed in Accipiter nisus (3.85%, 1/26), while Buteo japonicus showed the highest infection rate of E. bieneusi (33.33%, 1/3), followed by Asio otus (7.69%, 1/13). This study identified two Blastocystis sp. subtypes: ST3 and ST10 in raptors for the first time. Regarding E. bieneusi in raptors, we identified four genotypes: CHN-F1, HND-III, BEB6, and HLJD-I. Among these, BEB6 and CHN-F1 are notable for their zoonotic potential and the risk of waterborne outbreaks.DiscussionThese findings suggest that raptors may be potential transmitters of Blastocystis sp. and E. bieneusi to humans and other animals, as well as sources of water contamination. This study fills a gap in the research on Blastocystis sp. and E. bieneusi in raptors and is important for public health safety.